The Response of Wages and Labor Supply Movements to Employment Shocks Across Europe and the United States - Thomas, Alun (IMF Working Papers; Working Paper, 1994)
This paper assesses the responsiveness of wages and labor force movements to employment shocks across British and U.S. regions and across Europe using a multivariate vector autoregression technique. The paper finds inflexible real wages in all three areas in that each area's real wage responds very little to employment shocks. However, the response of the labor force to employment shocks is much greater in the United States compared to Europe. The strong labor force response in the United States prevents any persistence in relative regional unemployment rates whereas the lack of mobility in Europe results in persistent unemployment rate differentials across British regions and European nations. Europe must therefore adopt measures to reduce barriers to immobility if it is to succeed in moderating the persistence in relative unemployment rates.